Endogenous florendoviruses are major components of plant genomes and hallmarks of virus evolution - Geering, Andrew D. W.; Maumus, Florian; Copetti, Dario; Choisne, Nathalie; Zwickl, Derrick J.; Zytnicki, Matthias; McTaggart, Alistair R.; Scalabrin, Simone; Vezzulli, Silvia; Wing, Rod A.; Quesneville, Hadi; Teycheney, Pierre-Yves (Springer, 2014)
The extent and importance of endogenous viral elements have been extensively described in animals but are much less well understood in plants. Here we describe a new genus of Caulimoviridae called ‘Florendovirus’, members of which have colonized the genomes of a large diversity of flowering plants, sometimes at very high copy numbers (>0.5% total genome content). The genome invasion of Oryza is dated to over 1.8 million years ago (MYA) but phylogeographic evidence points to an even older age of 20–34 MYA for this virus group. Some appear to have had a bipartite genome organization, a unique characteristic among viral retroelements. In Vitis vinifera, 9% of the endogenous florendovirus loci are located within introns and therefore may influence host gene expression. The frequent colocation of endogenous florendovirus loci with TA simple sequence repeats, which are associated with chromosome fragility, suggests sequence capture during repair of double-stranded DNA breaks.